Eksistensi Feminisme Mesir dan Transformasi Gerakan Perempuan di Indonesia - Muhammad Fahmi Ilmy (LPPM IAIN Parepare, 2020)
Islamic feminism becomes an interesting issue when there are injustice and inequality in the functions and structures of life. The Egyptian state is part of the Middle East which inspired the reformist movement pioneered by Zainab Al Ghazali (1917-2005) by prioritizing preaching, social and political approaches. Given the organization view, there is support for the direction of the Indonesian women's movement to contribute to the country. The purpose of this research is to examine Islamic feminism in Egypt and to find out the direction of the Indonesian women's movement. This research uses qualitative research with a book-based literature study approach, official institution reports, and journals. The results showed that Islamic feminism in Egypt was oriented towards the socio-political field through preaching activities on the occurrence of injustice and differences in political views. Meanwhile, the direction of the Indonesian movement at the same time uses organized women through Aisyiyah and Muslimat with educational, economic, social, health and religious approaches that aim to seize independence and fill it up to this day. The implication is that the Islamic feminism movement, both in Egypt and Indonesia, have the same premise as an effort for the existence of women to contribute to life.